Uji Beda Rata-Rata Penerapan Corporate Social Responsibility Sebelum dan Saat Pandemi Covid-19 Pada Bank Syariah Mandiri - Erna Kurniya Wati; Endang Kartini Panggiarti (Jurnal Pendidikan Akuntansi (JPAK), 2021)
Corporate Social Responsibility is a social and environmental responsibility that must be carried out by companies, one of these companies is Islamic banking. This study aims to test whether there is an average difference in the implementation of Corporate Social Responsibility between before and during the Covid-19 pandemic at Bank Syariah Mandiri. This research is quantitative research using empirical studies. The data in this study uses secondary data obtained from the Annual Reports in 2019 and 2020. From this study, it was found that Bank Syariah Mandiri and Laznas-BSM collaborated in distributing Corporate Social Responsibility funds. The distribution is carried out with programs that are beneficial to the community such as the Mitra Umat, Educate Umat, and Simpati Umat. The number of samples used is only one Islamic banking, namely Bank Syariah Mandiri, the sample selection using purposive sampling technique. In addition to implementing the Corporate Social Responsibility program as set out, Bank Syariah Mandiri also contributed to dealing with the Covid-19 pandemic by distributing various kinds of assistance in the form of distribution of Personal Protective Equipment (PPE), masks, and food packages. Based on the results of the average difference test that has been carried out using the Pairet t-test, so it is known that there is an average difference in the distribution of Corporate Social Responsibility funds at Bank Syariah Mandiri before and during the Covid-19 pandemic.